Waldenström's macroglobulinemia: Two malignant clones in a monoclonal disease? Molecular background and clinical reflection - Growková, Kateřina; Kryukova, Elena; Kufová, Zuzana; Filipová, Jana; Ševčíková, Tereza; Říhová, Lucie; Kaščák, Michal; Kryukov, Fedor; Hájek, Roman (European journal of haematology, 2017)
Waldenström's macroglobulinemia (WM) is a complex disease characterized by apparent morphological heterogeneity within the malignant clonal cells representing a continuum of small lymphocytes, plasmacytoid lymphocytes, and plasma cells. At the molecular level, the neoplastic B cell-derived clone has undergone somatic hypermutation, but not isotype switching, and retains the capability of plasmacytic differentiation. Although by classical definition, WM is formed by monoclonal expansion, long-lived clonal B lymphocytes are of heterogeneous origin. Even more, according to current opinion, plasma cells also conform certain population with pathogenic and clinical significance. In this article, we review the recent advances in the WM clonal architecture, briefly describe B-cell development during which the molecular changes lead to the malignant transformation and mainly focus on differences between two principal B-lineage clones, including analysis of their genome and transcriptome profiles, as well as immunophenotype features. We assume that the correct identification of a number of specific immunophenotypic molecular and expression alterations leading to proper aberrant clone detection can help to guide patient monitoring throughout treatment and successfully implement therapy strategies directed against both B- and plasma cell tumor WM clones.
Keywords: imunofenotypizace; regulace genové exprese u nádorů; Genetic Heterogeneity; Signal Transduction; Humans; klonální evoluce; genetická heterogenita; zvířata; genetická variace; Clonal Evolution; Waldenstrom Macroglobulinemia; Phenotype; signální transdukce; B-Lymphocytes; plazmatické buňky; Plasma Cells; fenotyp; Gene Expression Regulation, Neoplastic; Immunophenotyping; Genetic Variation; Tumor Burden; B-lymfocyty; Animals; tumor burden; lidé; Waldenströmova makroglobulinemie